Formal approaches to poetry : recent developments in metrics - Dresher, Bezalel E. (Bezalel Elan), 1950-; Friedberg, Nila, 1972- (Phonology and phonetics ;, 2006)
This book will create greater public awareness of some recent exciting findings in the formal study of poetry. The last influential volume on the subject, Rhythm and Meter, edited by Paul Kiparsky and Gilbert Youmans, appeared fifteen years ago. Since th.